At the Thresholds: Labor Organizing as Travesti-Trans Formal Workers in Argentina: Travesti and trans workers in the formal sector expand imaginaries about the relationship between TTNB people and work, contributing to broader labor struggles for all of society - Romero, Francisco Fernández; Laterra, Pato; Sánchez, Víctor (NACLA Report on the Americas, 2025)
The document discusses the experiences of travesti and trans workers in the formal sector in Argentina, highlighting their struggles and achievements in gaining recognition and access to formal employment. It explores the impact of labor quotas for travesti-trans people in the public sector, shedding light on the challenges they face, such as temporary hirings and transphobic treatment. The text also delves into the role of organizations like Zaguán TranSindical in advocating for the rights of TTNB workers and reshaping labor policies to be more inclusive and supportive of diverse identities.